A novel method for investigation of the impact of sterilization by gamma radiation on polycaprolactone scaffold - Hoseini, M.; Hamidi, S.; Mohammadi, A.; Salehi, E. (Frontiers in Physics, 2022)
Structural properties of materials irradiated with gamma rays, such as mechanical and physical properties, may be modified or reduced depending on the displacement damages. Apart from increasing or decreasing that property, damage may be desirable or not. This study investigates the effects of sterilization by gamma radiation on polycaprolactone (PCL) scaffolds. Using a code-based simulation method, MCNPX provides information on primary knock-on atoms, or PKAs, that cause damage. To access PKA information, a program has been developed called GAMMATRACK. These PKA data can be used as input for the SRIM code to analyze gamma damage systematically. The rate of damage caused by gamma radiation is calculated on the PCL target. The theoretical calculation method also has been used to confirm the results of the Monte Carlo method (MCNPX + SRIM code). The possibility of the displacement cascade can be ignored due to the low-energy PKAs and the thin target. It is realized that all displacements are due to single vacancies. The total number of hydrogens, carbons, and oxygen PKAs were obtained. It was found that the number of carbons PKA is more than the others, which causes three-dimensional polymer networks to be created. In the experimental analysis, it is necessary to know the appropriate depth of the sample for damage investigation. GAMMATRACK gives the gamma displacement damage graph along the length of the PCL. It shows a uniform distribution of displacement damage. The damage rate for the PCL target is calculated, and the results between the theoretical calculations and the Monte Carlo method (MCNPX + SRIM code) differ by about 17%.